Determinants of Gender-Based Violence in Nepal: A Review of Recent Evidence - Dhital, Krishna Prasad (NPRC Journal of Multidisciplinary Research, 2025)
Background: Gender-based violence (GBV) remains a major global public health and human rights challenge, significantly impacting women's health and well-being. In Nepal, GBV is a pervasive societal crisis, with impacts that undermine the nation's progress. Recent evidence indicates that GBV persists at high levels, affecting women and girls across various settings, including schools and homes.Objectives: This narrative review aims to synthesize recent evidence on GBV in Nepal, with a focus on examining its determinants across multiple ecological levels—including individual, relationship, household, community, and institutional factors—to inform evidence-based prevention programs and policy interventions.Methods: This review is based on a synthesis of recent literature, including national surveys and empirical studies. The analysis is guided by a socio-ecological model, which recognizes that GBV is influenced by factors operating at multiple levels, from individual beliefs to broader societal structures.Findings: The review confirms the high prevalence of GBV in Nepal. A recent cross-sectional study among secondary school female students in the Sarlahi district found that 45.33% had experienced lifetime GBV, broken down into psychological (39.56%), sexual (30.22%), and physical violence (16.89%). Key risk factors identified include:• Individual/Relationship Level: Husband's alcohol use and poor marital communication are significant risk factors for intimate partner violence (IPV).• Household Level: Economic stress, type of family, and gender-based discrimination within the family are associated with GBV experience.• Community & Societal Level: Patriarchal norms, gender-inequitable attitudes, and the intergenerational transmission of violence (e.g., witnessing violence as a child) are deeply entrenched drivers of GBV. Despite existing laws, services for survivors remain fragmented, and emotional abuse is often overlooked due to a lack of physical evidence.Conclusion: GBV in Nepal is a complex issue driven by interconnected factors across the socio-ecological spectrum. While physical and sexual violence are documented, psychological violence is highly prevalent yet frequently overlooked by support systems.Implication: There is an urgent need for a multi-sectoral approach to effectively prevent and respond to GBV. This should include:• Strengthening institutional frameworks and multi-sectoral response services.• Implementing community-based programs that challenge harmful gender norms and engage men and boys.Improving access to integrated services—including legal, psychosocial, and health support—for survivors, particularly in remote areas.